Elementary School and Pre-service Teachers Learning and Teaching Together Immersed in an English Community of Practice (2024)
ABSTRACT: This study explores the collaborative learning dynamics between elementary school teachers and pre-service teachers in an English community of practice. Using a qualitative case study approach, data were gathered from research journals, interviews, lesson plan reflections, and a focus group to examine teachers' beliefs and practices, co-teaching benefits and challenges, and the impact of communities of practice on professional development. Findings reveal that while elementary teachers face challenges with their language proficiency, like fear of mispronouncing words in English, they actively use technological and contextualized resources to enhance learning. Co teaching enables elementary teachers to learn new English teaching strategies and methods from pre-service teachers, while pre-service teachers gain classroom management skills from the elementary teachers. The community of practice fosters professional growth through active learning. This research highlights the potential benefit and challenges of communities of practice and co-teaching models for elementary school teachers and pre-service teachers to support their professional growth and improve elementary teachers’ confidence teaching English offering valuable insights for educators and policymakers.